A novel high-resolution 2D silicon array detector for small field dosimetry with FFF photon beams. (January 2018) - Biasi, G.; Petasecca, M.; Guatelli, S.; Hardcastle, N.; Carolan, M.; Perevertaylo, V.; Kron, T.; Rosenfeld, A.B.
Highlights: 2D monolithic silicon array detector with sub-millimetre spatial resolution. Characterization for small field relative dosimetry with FFF photon beams. OFs accurate within 3%. PDDs values accurate within 2%. In-plane, cross-plane, 2 diagonal dose profiles acquired simultaneously with OF. Abstract: Purpose: Flattening filter free (FFF) beams are increasingly being considered for stereotactic radiotherapy (SRT). For the first time, the performance of a monolithic silicon array detector under 6 and 10 MV FFF beams was evaluated. The dosimeter, named "Octa" and designed by the Centre for Medical Radiation Physics (CMRP), was tested also under flattened beams for comparison. Methods: Output factors (OFs), percentage depth-dose (PDD), dose profiles (DPs) and dose per pulse (DPP) dependence were investigated. Results were benchmarked against commercially available detectors for small field dosimetry. Results: The dosimeter was shown to be a 'correction-free' silicon array detector for OFs and PDD measurements for all the beam qualities investigated. Measured OFs were accurate within 3% and PDD values within 2% compared against the benchmarks. Cross-plane, in-plane and diagonal DPs were measured simultaneously with high spatial resolution (0.3 mm) and real time read-out. A DPP dependence (24% at 0.021 mGy/pulse relative to 0.278 mGy/pulse) was found and could be easily corrected for in the case of machine specific quality assurance applications. Conclusions: Results were consistent with those for monolithic silicon array detectors designed by the CMRP and previously characterized under flattened beams only, supporting the robustness of this technology for relative dosimetry for a wide range of beam qualities and dose per pulses. In contrast to its predecessors, the design of the Octa offers an exhaustive high-resolution 2D dose map characterization, making it a unique real-time radiation detector for small field dosimetry for field sizes up to 3 cm side.